Retrospective reports of strategic‐level managers: Guidelines for increasing their accuracy - Huber, George P.; Power, Danial J. (Strategic Management Journal, 1985)
Abstract Strategic management studies frequently involve obtaining retrospective data from strategic‐level managers. The use of this data acquisition methodology has received relatively little codification and little critical review or comment. This seems unfortunate, as discussion and codification of the methodology could be useful for those academic researchers and corporate staff who study strategic decisions and organizational processes and for those managers who may be asked to provide the retrospective data. This paper is an attempt to remedy the current state of affairs. In particular, the paper reviews several sources of the data inaccuracies that commonly affect retrospective data and offers guidelines for reducing the occurrence or magnitude of these inaccuracies.